Embryology of the non-recurrent laryngeal nerve and advancements in detection prior to surgery - Gregory, Harrison H. K.; Ferris, Baillie W. C. (International Surgery Journal, 2025)
The non-recurrent laryngeal nerve (NRLN) is an uncommon anatomical variant of the recurrent laryngeal nerve (RLN). A right-sided NRLN is exceedingly more common than a left-sided NRLN, and almost all are associated with abnormalities of the aortic arch, especially a right aberrant subclavian artery (ASCA). The NRLN has a strong embryological basis, resulting from the premature obliteration of the right fourth aortic arch. Absence of this structure during longitudinal development allows the laryngeal nerve to migrate superiorly, ultimately branching from the cervical vagus nerve without entering the mediastinum. Despite a low prevalence, the presence of a NRLN is associated with a six to eight-fold increase in iatrogenic injury during surgeries of the thyroid, parathyroid and carotid structures. Pre-operative ultrasound for identification of an ASCA and thus the presence of a NRLN has demonstrated a clinically-significant reduction in the risk of laryngeal nerve damage intra-operatively. Intraoperative nerve monitoring (IONM) has also been shown as an effective alternative approach for detection of a NRLN intra-operatively. Further prospective studies exploring the effectiveness of these strategies in identifying a NRLN would be beneficial.